Bilgi ve Verimlilik - Tıngöy, Özhan (İstanbul Kültür Üniversitesi Yayınları, 2003)
Bu yazı çerçevesinde, bilgi çalışmalarının sorunları üzerinde durulmaktadır. Bilişim teknolojilerini kullanarak verimliliği artırmak için çözüm yolları sunmaktadır. Bu amaçla çeşitli stratejiler bilişim teknolojisi kullanımıyla geliştirilerek verimlilik artışı sağlama yöntemleri üzerinde durulmaktadır. This article describes the productivity problem in information work by noting that there ara large differences among individuals, and that this amplified by an increasing percentage of workers in the information work class. This article discusses methods for improving productivity in information work by organizing information work around effectiveness and efficiency strategies.
Keywords: Bilişim Teknolojileri; Bilgi Çalışmalarında Verimlilik; Information Technology; Interest in The Work Efficiency